5G and beyond wireless transport technologies enabling backhaul, midhaul, and fronthaul - Morais, Douglas H. (Springer, 2021)
This text covers the key technologies employed in wireless links that enable increased data rates and thus are likely to be employed in support of 5G wireless transport networks, i.e., backhaul, midhaul, and fronthaul networks. The author presents technologies at an introductory level but nonetheless at a level that imparts to the reader a sound understanding of the fundamentals. The book is intended for those practicing engineers and graduate and upper undergraduate students who have an interest in acquiring, where missing, the necessary technology background in order to comprehend the functioning and capability of 5G based wireless transport links. The author focuses on those technologies that are key to achieving the high data rates and high reliability required of this transport. The material is presented in a clear, concise, and mathematically light fashion. Covers key wireless transport (backhaul, midhaul, and fronthaul) technologies for 5G and beyond, presented in a clear tractable fashion; Outlines the basic wireless transport transmitter/receiver terminal architecture, provides specifications of some such terminals, and indicates the link performance afforded by such terminals; Provides sufficient mathematics to make it technically coherent, but not so much as to make it challenging for a reader with no or limited familiarity with these technologies.